2009
DOI: 10.1590/s1519-69842009000100019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α-difluormethylornithine on Anastrepha fraterculus (Diptera, Tephritidae) ovary size

Abstract: Ovarian sizes (length and width) were measured in young females of Anastrepha fraterculus (Wiedemann) (Diptera, Tephritidae) subjected or not to the inhibitor α-difluormethylornithine (α-DFMO). The most effective concentration of α-DMFO used was 50 mM and the ovarian measurements (length and width) of the treated females were smaller than those of females not treated with α-DMFO. These data may suggest some relationship between ornithine decarboxylase (ODC) and sexual maturation in A. fraterculus.Keywords: Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The RNAi‐driven depletion of ODC also strongly impaired nitrogen metabolism and reproduction in blood‐fed A. aegypti females. It was previously reported that the administration of DFMO negatively impacts insect reproduction 16,17,22,25 . Oocyte development was inhibited in A. aegypti females fed an artificial BM supplemented with 75 mM DFMO 25 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The RNAi‐driven depletion of ODC also strongly impaired nitrogen metabolism and reproduction in blood‐fed A. aegypti females. It was previously reported that the administration of DFMO negatively impacts insect reproduction 16,17,22,25 . Oocyte development was inhibited in A. aegypti females fed an artificial BM supplemented with 75 mM DFMO 25 .…”
Section: Discussionmentioning
confidence: 96%
“…It was previously reported that the administration of DFMO negatively impacts insect reproduction. 16,17,22,25 Oocyte development was inhibited in A. aegypti females fed an artificial BM supplemented with 75 mM DFMO. 25 A reduction in midgut trypsin activity and a decrease in DNA, RNA, polyamine, and Vg synthesis were also observed in blood-fed A. aegypti females treated 25 Digestive serine proteases such as LT and 5G1 trypsins play a major role during BM protein digestion in A. aegypti.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation